Histopathological and cytotoxic changes induced by spinosad on midgut cells of the non-target predator Podisus nigrispinus Dallas (Heteroptera: Pentatomidae). (January 2020) - Santos Junior, Valdeir Celestino dos; Martínez, Luis Carlos; Plata-Rueda, Angelica; Fernandes, Flávio Lemes; Tavares, Wagner de Souza; Zanuncio, José Cola; Serrão, José Eduardo
Abstract: Broad-spectrum insecticides used in pest control are a risk for non-target insects. Their compatibility to the insecticide spinosad, used in agriculture and forestry as a biological control tool, needs to be evaluated. Podisus nigrispinus Dallas (Heteroptera: Pentatomidae) is a predatory bug used in the pest management of agricultural and forest systems where spinosad is also frequently applied. The aim of this study was to evaluate the toxicity, histopathology and cytotoxicity in midgut cells of P. nigrispinus exposed to spinosad. The toxicity test was performed to determine the lethal concentrations of spinosad after exposure by ingestion. The histopathology and cytotoxicity caused by spinosad were analyzed in the three midgut regions (anterior, middle and posterior) of P. nigrispinus during different exposure periods. Spinosad, at low concentrations, was toxic to P. nigrispinus [LC50 = 3.15 (3.02–3.26) μg.L −1 ]. Cell degeneration features such as cytoplasm vacuolization, chromatin condensation and release of cell fragments to the midgut lumen were observed in this organ. Cell death via apoptosis was found in the three midgut regions of this predator after exposure to the insecticide. Spinosad is toxic to P. nigrispinus, and causes histological and cytological damage followed by cell death in the midgut, suggesting a dangerous effect on a beneficial non-target insect. Highlights: The predatory bug, Podisus nigrispinus is used to control agricultural and forestry pests. Toxicity, histopathology, and cytotoxic changes by spinosad were evaluated in the midgut. Cytotoxic effects were cytoplasm vacuolization, cell fragment, and autophagy. Spinosad induces apoptosis on midgut cells via ingestion after 24 h exposure. Spinosad has side-effect in the midgut and can't be used simultaneously with this predator.